Analysis of tribo-charging during powder spreading in selective laser sintering: Assessment of polyamide 12 powder ageing effects on charging behavior - Hesse, Nicolas; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Lübbert, Christian; Roth, Stephan; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2019)
Powder flowability is key to achieving high process stability and part quality by application of smooth and dense layers in selective laser sintering (SLS). This study sheds light on the rarely investigated effect of tribo-electric charge build-up during powder delivery in the SLS process. This is achieved by a novel approach to quantify electrostatic potentials during doctor blading. The presented model setup is used in combination with charge spectrometry and impedance spectroscopy to investigate the alterations in tribo-electric charging behavior for the most commonly used laser sintering material polyamide 12 in its virgin and aged, c.f. reused, states. We show that the electrostatic charge build-up is significantly enhanced for aged polymer powder material, likely contributing to altered performance in SLS processing.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Additive manufacturing; Charge distribution; Electrostatics; Polyamide 12; Polymer ageing; Powder layer formation; Selective laser sintering; Surface potential; Tribo-charging

A step closer to continuous buffer preparation from solids: Predicting powder compaction and how to prevent it - Komuczki, D.; Hesse, Nicolas; Schmidt, Jochen; Satzer, P. (New Biotechnology, 2023)
The preparation of buffer solutions used in the biopharmaceutical industry is typically performed manually by the addition of one or multiple buffering reagents to water. Recently, the adaptation of powder feeders for continuous solid feeding was demonstrated for continuous buffer preparation. However, the intrinsic characteristics of powders can change the stability of the process, due to the hygroscopic nature of some substances and humidity-induced caking and compaction behavior, but there is no simple and easy methodology available for predicting this behavior for buffer species. To predict which buffering reagents are suitable without special precautions and investigate their behavior, force displacement measurements were conducted with a customized rheometer over 18 h. While most of the eight investigated buffering reagents indicated uniform compaction, especially sodium acetate and dipotassium hydrogen phosphate (K2HPO4) showed a significant increase in yield stress after 2 h. Experiments conducted with a 3D printed miniaturized screw conveyor confirmed the increased yield stress measurements by visible compaction and failure of the feeding. By taking additional precautions and adjusting the design of the hopper, we demonstrated a highly linear profile of all buffering reagents over a duration of 12 and 24 h. We showed that force displacement measurements accurately predict the behavior of buffer components in continuous feeding devices for continuous buffer preparation and are a valuable tool to identify buffer components that need special precautions. Stable, precise feeding of all tested buffer components was demonstrated, highlighting the importance of identifying buffers that need a specialized setup with a rapid methodology.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Ball indentation; Buffers; Chromatography; Pharmaceutical; Powder

Biodegradable Polylactide Supraparticle Powders with Functional Additives for Biomedical Additive Manufacturing - Canziani, Herbert; Hanschmann, Benedikt; Tischer, Florentin; Sommereyns, Alexander; Distler, Thomas; Schramm, Jonas; Hesse, Nicolas; Schmidt, Jochen; Grünewald, Alina; Detsch, Rainer; Boccaccini, Aldo R.; Maskos, Michael; et al. (Advanced Functional Materials, 2022)
Additive manufacturing, in particular powder bed-based fabrication processes hold promise to revolutionize biomedical engineering for the ability to provide customized, functional implants, for example as bone replacement materials. However, providing functional powder particles that unify material requirements for biodegradable and bioactive biomaterials and process requirements to enable successful powder bed fusion remains an unmet challenge. Here, a supraparticle-based approach to create biodegradable poly(lactic acid) and composite powders for the additive manufacturing of bone replacement materials is introduced. Colloidal binary Ca-SiO2 glasses and hydroxyapatite are incorporated as bioactive functional additives to support the formation of bone-like calcium phosphate. The supraparticle powders are prepared by a scalable spray-drying process, which offers control of particle size, shape, and composition. All process-relevant powder characteristics are analyzed as a function of composition and structure, including flowability, thermal, and melt rheological properties. The optimized supraparticle powders are successfully used in the process of laser powder bed fusion of polymers to prepare macroscopic specimens via additive manufacturing. It is demonstrated that the material combination of the composites provides relevant functional properties, including biodegradation and bioactivity. The process provides a flexible and adjustable toolbox for the design of functional powders toward biomedical additive manufacturing.<br
Keywords: 3D printing; additive manufacturing; biomaterials; PLA; powder bed fusion; spray drying; supraparticles

Characterization of Polymer Powders for Selective Laser Sintering - Schmidt, Jochen; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Hesse, Nicolas; Bück, Andreas; Peukert, Wolfgang (Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium 2019, 2019)

Enhancement of polyamide laser sinter powder reusability by acid catalyzed hydrolysis - Hesse, Nicolas; Peukert, Wolfgang; Schmidt, Jochen (Procedia CIRP, 2020)
This contribution introduces a method to reverse the deterioration in melt rheological behaviour (‘ageing’) of polyamide 12 that has previously been used in powder bed fusion processing by reduction of the polymers molecular weight via acid catalysed hydrolysis. Chosen hydrolysis conditions allow for a reconditioning below melting temperature and therefore leave the particulate nature of the powder intact while significantly improving the polymers rheological properties. The influences of different temperatures, acids and pH-values are investigated and the processability of recycled powders is assessed by melt rheological, optical and thermal characteristics.
Keywords: powder bed fusion; selective laser sintering; polyamide 12; powder reusability; hydrolysis; molecular chain length; zero shear viscosity

From trash to treasure in additive manufacturing: Recycling of polymer powders by acid catalyzed hydrolysis - Hesse, Nicolas; Jaksch, Andreas; Kaschta, Joachim; Groh, Dominik; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2023)
A persistent problem in laser powder bed fusion (PBF) additive manufacturing (AM) of polymers is the accumulation of used feedstock material that cannot be reprocessed due to alterations in the physical and chemical structure upon ageing at elevated temperatures. The chemical ageing of polyamide 12, the most frequently used feedstock in PBF of polymers, occurs due to solid-state post-condensation during the AM process and can be reversed by appropriate processing. This paper investigates the application of acid-catalyzed hydrolytic reconditioning to restore virgin powder properties from used and annealed feedstock material, highlighting a pathway to more sustainability in AM. The proposed method is optimized towards PBF-printing relevant properties and mechanical characteristics of parts build with the recycled feedstock material, which are benchmarked against conventional powder refreshing strategies.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Hydrolysis; Polyamide 12; Polymer ageing; Polymer recycling; Powder bed fusion; Powder characterization

Human laryngeal mucus from the vocal folds: Rheological characterization by particle tracking microrheology and oscillatory shear rheology - Peters, Gregor; Wendler, Olaf; Böhringer, David; Gostian, Antoniu Oreste; Müller, Susanna; Canziani, Herbert; Hesse, Nicolas; Semmler, Marion; Berry, David A.; Kniesburges, Stefan; Peukert, Wolfgang; Döllinger, Michael (Applied Sciences, 2021)
Mucus consistency affects voice physiology and is connected to voice disorders. Neverthe-less, the rheological characteristics of human laryngeal mucus from the vocal folds remain unknown. Knowledge about mucus viscoelasticity enables fabrication of artificial mucus with natural properties, more realistic ex-vivo experiments and promotes a better understanding and improved treatment of dysphonia with regard to mucus consistency. We studied human laryngeal mucus samples from the vocal folds with two complementary approaches: 19 samples were successfully applied to particle tracking microrheology (PTM) and five additional samples to oscillatory shear rheology (OSR). Mucus was collected by experienced laryngologists from patients together with demographic data. The analysis of the viscoelasticity revealed diversity among the investigated mucus samples according to their rigidity (absolute G’ and G”). Moreover some samples revealed throughout solid-like character (G’ > G”), whereas some underwent a change from solid-like to liquid-like (G’ < G”). This led to a subdivision into three groups. We assume that the reason for the differences is a variation in the hydration level of the mucus, which affects the mucin concentration and network formation factors of the mucin mesh. The demographic data could not be correlated to the differences, except for the smoking behavior. Mucus of predominant liquid-like character was associated with current smokers.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Human laryngeal mucus; Oscillatory shear rheology; Particle tracking microrheology; Viscoelasticity; Vocal folds

Kunststoffpulver für die Additive Fertigung: Vorhersage des Prozessverhaltens mittels prozessangepasster Analyse / Plastic powder for Additive Manufacturing: Prediction of process behavior based on process adapted characterization - Wudy, Katrin; Schmidt, Jochen; Lanzl, Lydia; Zhao, Meng; Jaksch, Andreas; Dechet, Maximilian; Hesse, Nicolas; Drummer, Dietmar; Peukert, Wolfgang (Vom Pulver zum multifunktionalen Bauteil, 2019)

Selektives Laserstrahlschmelzen von Kunststoffen: Lokale Bauteileigenschaften in Abhängigkeit unterschiedlicher Alterungszustände des Ausgangspulvers - Jaksch, Andreas; Hesse, Nicolas; Drummer, Dietmar; Schmidt, Jochen (6. Industriekolloquium des SFB 814, 2018)

Selektives Laserstrahlschmelzen von Polyamid 12 - Einfluss von Fließhilfsmitteln auf Verarbeitbarkeit und Bauteileigenschaften - Jaksch, Andreas; Hesse, Nicolas; Schmidt, Jochen; Drummer, Dietmar (Proceedings of the 17th Rapid.Tech Conference, 2021)

Towards a generally applicable methodology for the characterization of particle properties relevant to processing in powder bed fusion of polymers – from single particle to bulk solid behavior - Hesse, Nicolas; Winzer, Bettina; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2021)
The majority of additively manufactured plastic parts built with powder bed fusion (PBF) processes are made of polyamide 12. Since only a fraction of powder ends up in the components built, part cake material and overflow powder has to be re-used for economic and ecologic reasons, even though its material properties are altered by thermo-mechanical stress during processing. Changes in bulk solid properties play a key role for the stability of the PBF process and the quality of manufactured parts. However, there is still no generally accepted method for the evaluation of used powders with respect to their processability and a lack of understanding of underlying bulk material mechanics. The aim of this study, exemplified for polyamide 12, is to assess widely applicable, standardized and process-adapted characterization methods in additive manufacturing and to shed light on the underlying phenomena causing the changes in flowability and packing properties of used powders.<br
Keywords: Powder bed fusion; Powder characterization; Powder flowability; Powder aging; Polyamide 12